Push, Pass, Pull Political Marketing Adnan Purichta Ichsan-Abdul Rauf Mallagani Pada Pemilihan Kepala Daerah di Kabupaten Gowa 2015 - khaerah, nur; rusnaedy, zaldi (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2019)
This article analyzes Push, Pass, Pull Political Marketing Adnan Purichta Ichsan-Abdul Rauf Mallagani At the Election of Regional Heads in Gowa Regency 2015. This study uses qualitative research methodology, with data obtained through interviews, literature studies and documentation. The analysis technique uses data reduction, data presentation, and conclusion drawing. The results of the study show that 1). The results of the electability survey of JSI, LSI and IPI as well as the vision and mission that are used as selling political products can ultimately give influences to the formation of public opinion, so that voters solidify their choice of candidates who are marketed. This push-marketing strategy is carried out as a rational and emotional stimulant to voters. 2). The involvement of Ichsan's character in the political marketing pass strategy by Adnan's team was able to become the ideal influencer for rational voters and loyalists of Yasin Limpo's family in the 2015 Gowa Regency Election. 3) Strategy Pull Political Marketing whose expectations for forming Adnan's image is not optimal due to Ichsan's under the shadow. Even so, there are still efforts to form a positive political image. One of them is through branding on various media especially social media.Keywords: Push, Pass, Pull Political Marketing; Winning Strategy, Local Election